MISI KRISTEN DI TENGAH KEMAJEMUKAN AGAMA: TANTANGAN DAN PELUANG UNTUK PERDAMAIAN - Yohanes Kristian Labobar; Fredrik Warwer; Bernard Labobar (Sekolah Tinggi Teologi Arastamar Bengkulu, 2025)
Christian mission in the midst of religious pluralism presents both challenges and opportunities to create peace. The church is called to proclaim the love of Christ to all people regardless of cultural, racial, ethnic and religious differences. In the context of pluralism, the biggest challenge is how to communicate the gospel message without causing conflict with other beliefs. However, this also opens up opportunities to strengthen interfaith dialog and strengthen tolerance. A qualitative method with a literature study approach is used to examine Christian mission in a pluralistic society. The Christian mission to live harmoniously in a religiously plural society is important and meaningful. The church has been wise in positioning itself and carrying out its role. The church has realized that the condition of religious pluralism is very vulnerable and easily triggers conflict. By understanding the insights of exclusivism, inclusivism, and pluralism, as well as the various opinions/thoughts that have been described above, the Church should not be trapped in radical groups but be increasingly wise in positioning itself appropriately and holding fast to biblical truth so that its role is elegant for all.